Procurement in the age of automation : automated negotiations can cause anxiety among business leaders, buyers, and suppliers despite the benefits. Here's how to overcome resistance - Hoek, Remko van; Lacity, Mary Cecelia (MIT Sloan Management Review, 2023)
Companies that have successfully automated their procurement negotiations are gaining a wide range of benefits, including cost savings, increased supply chain resilience, and access to an expanded pool of qualified suppliers. However, implementing a new procurement model and a different approach to relationships isn’t easy. Six key practices are needed to address legitimate concerns and overcome resistance from business unit leaders, buyers, and suppliers.